Effects of Drug Transporters on Pharmacological Responses and Safety - Liu, Chang-Xiao; Yi, Xiu-Lin; Fan, Hui-Rong; Wu, Wei-dang; Zhang, Xing; Xiao, Xue-Feng; He, Xin (Current Drug Metabolism, 2015)
Recently, it is realized that transporters, apart from enzymes, play a key role in drug metabolism and pharmacokinetics. More and more pharmaceutical researchers focused on transporter study and found that drug transporters not only involved in pharmacokinetics including absorption, distribution, metabolism and excretion (ADME) but also in Drug-Drug interactions (DDIs). DDIs induced by drug transporters are the important safety evaluation factors which have to be taken into account at stage of drug discovery and development. Therefore, it should pay more attention to the studies on step of preclinical and clinical trial. In this review, the author focused on the effects of drug transporters on pharmacological and safety responses, such as the effects on plasma elimination half-lives, on drug accumulation in body after repeated dosing, on potentiating either pharmacological or adverse effects and molecular mechanisms of transporter-mediated DDIs. Present studies showed that DDIs involving the drug transporters including ABC transporters, organic anion and cation transporters, peptide transporters, monocarboxylate transporters, nucleoside transporters and folate transporters, and the possible side effects derived from clinical combination therapy must pay attention. The author also discussed the molecular mechanisms of transporter-mediated DDIs by the data obtained from preclinical and clinical studies, and inferred the available curative effects and the potential risk of the drug combination involving these drug transporters, which provides a reference for the safety of clinical medication and a consideration for a successful drug discovery. This article carefully reviewed transporter-based DDIs and highlighted areas that DDIs were poorly predicted through transporters or areas are still confronted with challenges in future.
Keywords: pharmacokinetics